1. J

    Relation Algebra, why is this PDL sentence equivalent

    In the book modal logic for open minds by johan van benthem there is on page 161 a statement that the sentence $\langle (R\lor S)* \rangle \phi$ is equivalent to the sentence $\langle (R* ; S*)* \rangle \phi$ (* means iteration and ; means composition here) So: $\langle (R\lor S)* \rangle...
  2. J

    Propositional dynamic logic why is this valid?

    I have been reading the paper:Propositional dynamic logic(PDL) with Belnapian truth values. In PDL these sentences are valid: $\left[a \cup b\right]p \equiv (\left[a\right]p \land \left[b\right]p)$ But why is that? Because if we take for instance: $\left[a \cup b\right]p$, is...